CONTRIBUTION TO THE STUDY OF THE HYGENIC CONDITION OF GREEK CHEESES - ΣΚΟΥΝΤΖΟΣ, Κ.; ΠΑΠΑΔΙΑ, Α.; ΓΙΩΤΗ, Α. (Journal of the Hellenic Veterinary Medical Society, 1973)
801 samples of various types of Greek cheese (fêta, kefalotyrion, gruyère and kasserion) obtained from the Attican area were examined. The contained numbers of coliforms, intestinal colibacilli and pathogenic staphylococci were determined, and the presence of Salmoncllae was investigated. It was revealed that 22.11%, 28.88%, 11.48% and 0.94% of feta, kefalotyrion, gruyère and kasserion samples, respectively, contained more than 100 intestinal colibacilli per gram sample; furthermore, 19.84%, 22.21 %, 10.56% and 0.95% of the same samples contained more than 1.000 coliforms per gram sample. In 1.99% and 0.52% of feta and kasserion samples, respectively, the presence of pathogenic staphylococci was established, whereas SQ .lmonellae were not found in any of the cheese samples examined. The establishment of criteria for the definition of the hygenic condition of Greek cheeses, as well as for their uniform testing technique is proposed.